Perceptions and Factors Affecting Patient Safety Culture of Employees in Pediatric Services - Yüksel Karademirler; Gülay Manav (Galenos Yayinevi, 2020)
Aim:In this study, some factors affecting the patient safety culture and perceptions of health care workers working in pediatric clinics were examined.Materials and Methods:This descriptive type of research was conducted with a total of 461 health care workers.Results:36.2% of these healthcare workers were aged 26-35 and 54.8% were working as nurses. The hospital health workers patient safety culture survey showed that they reached an overall score of 51% in the hospital survey. Employees received the highest positive response from "in-unit teamwork" sub-dimension with 71.55% and the lowest positive response from "non-punitive response to error" sub-dimension with 28.06%. It was determined that the majority of healthcare workers working in pediatric services knew the concept of patient safety and implemented patient safety initiatives while providing care.Conclusion:As a result, it is recommended that the patient safety culture levels of the employees should be continuously evaluated between the institution and the employees.